Morphological complexity within and across boundaries in honour of Asli Göksel - Göksel, Asli; Gürer, Asli; Uygun Gökmen, Dilek; Öztürk, Balkiz (Studies in language companion series (SLCS),, 2020)
"This volume brings together a collection of original articles investigating state-of-the-art themes in morphology. The papers in the volume provide an in-depth analysis for spoken and sign languages within morphological word domain, morphosyntax and morphophonology. Bringing data from a variety of languages including Turkish, some understudied ones (e.g. Turkish Sign Language, Late Ottoman Turkish) and also endangered languages (e.g. Karachay-Balkar, Sauzini, Cappadocian, Aivaliot and Pharasiot Greek), the volume will be of special interest to a wide audience ranging from typologists to theoretical linguists and graduate students in linguistics and is expected to generate further research on the above mentioned languages, as well as to contribute to the cross-linguistic literature on the themes explored in the volume"--